Studi Eksplorasi Dimensi Pelayanan Administrasi (KK, KTP, dan Akta Kelahiran) Kantor Desa Bungae Jaya Kecamatan Pallangga Kabupaten Gowa - Akil, Nasriah; Misbahuddin; Taufik, Imran; Guntur, Ihsan; Abdullah (STIM-LPI Makassar, 2024)
This research was conducted in Gowa Regency by exploring administrative services (KK, ID cards, and birth certificates) as an effort to improve services to the community. The sample in this research was in accordance with the needs based on administrative service providers and their users and the sampling used was based on the setting. Cresswell 1998, after conducting interviews regarding the responses and expectations received, it was continued with validity and reliability tests The results of this research show that the attitude of professionalism that is built by the creativity of each employee in a regional agency by using the facilities as well as possible reflects the service they provide.